"Dependence of Mesomorphism in Combination with Fluoro and Chloro Groups". (2nd November 2018) - Ranchchh, Avani R.; Tharesha, Bhavna R.; Bhoya, U.C.
Abstract: A novel azoester homologous series with chloro lateral group and a fluoro terminal end group was synthesized and characterized for mesomorphic properties. It consists of thirteen azo ester derivatives from trans-4-n-alkoxy cinnamic acid with 4-hydroxy-3-chloro phenyl azo-3-chloro-4-fluoro benzene. Mesomorphic property commences from C4 homologue as smectic.C1 to C3 member of the series are non-mesomorphic. C4 to C18 homologous are enantiotropic smectic A phase. The nematic mesophase is totally absent. Texture and transition temperatures of the homologues are determined by an optical polarizing microscopy equipped with heating stage. 1 H NMR, IR spectra, mass spectra, of some member is included. The spectroscopic analysis supports the molecular structure. A phase diagram is used to illustrate the mesomorphic behaviour across the series. Mesophaselength for smectic is varying from18.0 ° C to 69.0 0 C. Mesomorphic properties of the novel azoester series are compared with structurally similar series.